73‐2: A Wide View Glass‐less 3D Display with Head‐Tracking System for Horizontal and Vertical Directions. Issue 1 (May 2016) - Suzuki, Daichi; Koito, Takeo; Kasai, Taiki; Sugiyama, Hiroki; Hayashi, Shuji; Watabe, Hiroyuki; Nakao, Takayuki; Ozeki, Yoshitaka; Tanase, Kenji; Mizuhashi, Hiroshi; Ito, Masayuki
Abstract : In this study, a glass‐less 3D display with a head‐tracking system for horizontal and vertical directions was developed. Based on the viewer's head position, the barrier pitch and the position of the barrier aperture were optimized. This resulted in the expansion of the 3D viewing zone in a vertical direction from the display surface to the distance of "320 – 1016 mm", and in the horizontal direction from the center of the display at a "±267 mm" distance.